Occurrence of alkali-labile sites in pulse labelled DNA of Escherichia coli after the action of DNA-damaging chemicals - Slezáriková, V; Sedliaková, M (Folia microbiologica, 1987)
UV irradiated E. coli cells contain alkali labile sites in their DNA daughter chains. It is shown here that the occurrence of alkali labile sites in the newly synthesized DNA is a more common phenomenon. It occurred after treatment with two different DNA damaging chemicals, but not after treatment with nalidixic acid.
Keywords: mitomycin; poškození DNA; DNA Damage; Methylnitrosourea; Mitomycin; methylnitrosomočovina; DNA bakterií; mitomyciny; DNA, Bacterial; Escherichia coli; Mitomycins; Nalidixic Acid; kyselina nalidixová